Geneza artystyczna pomnika grobowego Józefa Frageta na Starych Powązkach w W arszawie - Wiraszka, Marta (Saeculum Christianum. Pismo Historyczne, 2016)
Neoclassical mausoleum of Józef Fraget (1797-1867) commemorating a French industrial entrepreneur and the founder of the first factory of clad goods in Poland was constructed at Old Powązki Cemetery in Warsaw between 1867 and 1869 (quarter A, row I). The author of the torso is Leonard Marconi, and the mold is believed to have been made by the “Lilpop, Rau i Loewenstein” factory in Warsaw. The original project embraced only the top, cast iron part of the tomb in the form of Doric aedicule with entablature and triangular pediment as well as the marble torso placed on prism pedestal located among four columns. The bottom, stone part, was executed later, approximately in 1913 in Władysław Tuszyński stone enterprise. The Mausoleum of Fraget is a replica of the monument situated in Berlin at St. Dorothy’s Cemetery commemorating Johann August Borsig (1804-1854), the owner of the well-established metal factory in Europe. Its designer was an architect from Berlin, an apprentice of Schinkl, Johann Heinrich Strack, and the maker of the bronze torso mold was a sculptor Christian Daniel Rauch. Three other mausoleums originated from the same model: the Brand family mausoleum at the Metallurgical Cemetery in Gliwice, (between 1865 and 1890), Tomas Evans mausoleum at the Evangelical Reformed Cemetery in Warsaw (second half of the 60s. the XIX century, currently non-existent) and in its slightly modified form, the tomb of the architect J. H. Strack at the St Dorothy’s Cemetery in Berlin (1880-1882). All the above-mentioned mausoleums except the monument decorating the tomb of the architect Strack, commemorated personalities from metallurgical industry. The particularity of the mausoleum of Józef Fraget consists in the use of cast iron as the main constructing element. It is a distinctive feature differing the mausoleum in question from the remaining exemplary monuments made of stone.